In-vivo monitoring of acute DSS-Colitis using Colonoscopy, high resolution Ultrasound and bench-top Magnetic Resonance Imaging in Mice. - Walldorf, J; Hermann, M; Porzner, M; Pohl, S; Metz, H; Mäder, K; Zipprich, A; Christ, B; Seufferlein, T (European Radiology, 2015)
Objective: The aim of this study was to establish and evaluate (colour Doppler-) high-resolution-ultrasound (hrUS) and bench-top magnetic resonance imaging (btMRI) as new methods to monitor experimental colitis.Materials and Methods: hrUS, btMRI and endoscopy were performed in mice without colitis (n = 15), in mice with acute colitis (n = 14) and in mice with acute colitis and simultaneous treatment with infliximab (n = 19).Results: Determination of colon wall thickness using hrUS (32 MHz) and measurement of the cross-sectional colonic areas by btMRI allowed discrimination between the treatment groups (mean a vs. b vs. c - btMRI: 922 vs. 2051 vs. 1472 pixel, hrUS: 0.26 vs. 0.45 vs. 0.31 mm). btMRI, endoscopy, hrUS and colour Doppler-hrUS correlated to histological scoring (p < 0.05), while endoscopy and btMRI correlated to post-mortem colon length (p < 0.05).Conclusions: The innovative in vivo techniques btMRI and hrUS are safe and technically feasible. They differentiate between distinct grades of colitis in an experimental setting, and correlate with established post-mortem parameters. In addition to endoscopic procedures, these techniques provide information regarding colon wall thickness and perfusion. Depending on the availability of these techniques, their application increases the value of in vivo monitoring in experimental acute colitis in small rodents.Key Points: • Improved in vivo monitoring might balance interindividual differences in murine colitis. • In monitoring murine colitis, btMRI and hrUS are safe and technically feasible. • Very short examination times underline the usefulness especially of hrUS. • Results of btMRI and hrUS correlate with endoscopic and post-mortem findings.